Óleos essenciais de quatro espécies nativas de Piper : Piper caldense C. DC., P. solmsianum C. DC., P. umbellatum L. e P. xylosteoides Kunth - Maduro, Carlos Eduardo Piemontez, 1980- (2019)
Orientadora: Prof.ª Dr. ª Beatriz Helena L. de N. Sales Maia